Organic Fouling Behavior and Mechanisms in Nanofiltration Membranes for Water Treatment Processing - (:unkn) unknown (My University, 2023)
Nanofiltration membrane technology is an expanding topic of interest for use in water treatment processes, particularly in the elusive field of desalination. Desalination is becoming more and more necessary as climate-change related weather events like droughts, and populations in water scare areas both increase. Reverse osmosis membrane systems are a reliable, but costly method for removing salts from otherwise unusable saline water sources. One way to decrease the cost of these systems is by utilizing porous membranes, like ultrafiltration or nanofiltration membranes, for pretreatment. Additionally, nanofiltration has recently shown promise as an effective alternative to reverse osmosis in desalination systems.The main cause of concern in membrane systems is fouling, which has many different causes and manifestations in real-world scenarios. Fouling causes a decline in the membrane’s flux over time and lowers the membrane’s lifespan. A more robust understanding of the many complexities of membrane fouling can help to better prevent and treat fouling in a system. This can reduce the overall system costs by reducing cleaning time, increasing membrane lifespans, and decreasing energy requirements. This study compared two nanofiltration membranes – commercially manufactured NF270 membranes, and lab-synthesized Covalent Organic Framework (COF) membranes – analyzing their fouling behaviors and mechanisms, during high-concentration organic fouling. Fouling rate, fouling mechanisms and models, and limiting flux were explored.
Keywords: Desalination; Fouling; Membrane; Nanofiltration